The Arabidopsis – Plasmodiophora brassicae interaction - Drost, Sytske (2015)
Clubroot, caused by the obligate biotrophic protist Plasmodiophora brassicae, is an important disease of Brassica oil and vegetable crops, and causes an estimated production loss of 10% worldwide. Infected root tissues develop swollen roots (clubroots) leading to wilting, stunting and premature ripening of the aboveground organs. During infection, P. brassicae interferes with the metabolism and hormone homeostasis of the host to avoid plant defense responses. The aim of this thesis was to study the role of several host genes in the disease response in an Arabidopsis thaliana – P. brassicae infection system. The investigated genes are involved in brassinosteroid (BR) biosynthesis and signaling, the jasmonic acid (JA) and salicylic acid (SA) defense pathway, and in lipid transport. BRs are plant hormones essential for cell expansion and elongation. GUS-reporter strains of A. thaliana revealed an increased expression of BR signaling and biosynthesis genes in clubroots. We showed that BR signaling and biosynthesis in the host might play an important role for the disease development in infected tissues. Roots infected with P. brassicae contained a high amount of lipid bodies. Lipids might be synthesized de novo in the clubroots, as the proLTP1a-GUS and proLTP1b-GUS showed increased GUS expression only at early infection stages. Defense-related JA and SA GUS marker genes did not markedly induce GUS expression in infected tissues, implying that P. brassicae avoids host defense responses.